SOD1 is a synthetic-lethal target in PPM1D-mutant leukemia cells - Zhang, Linda; Hsu, Joanne I; Braekeleer, Etienne D; Chen, Chun-Wei; Patel, Tajhal D; Martell, Alejandra G; Guzman, Anna G; Wohlan, Katharina; Waldvogel, Sarah M; Uryu, Hidetaka; Tovy, Ayala; Callen, Elsa; et al. (eLife, 2024)
The DNA damage response is critical for maintaining genome integrity and is commonly disrupted in the development of cancer. PPM1D (protein phosphatase Mg 2+ /Mn 2+ -dependent 1D) is a master negative regulator of the response; gain-of-function mutations and amplifications of PPM1D are found across several human cancers making it a relevant pharmacological target. Here, we used CRISPR/Cas9 screening to identify synthetic-lethal dependencies of PPM1D, uncovering superoxide dismutase-1 (SOD1) as a potential target for PPM1D -mutant cells. We revealed a dysregulated redox landscape characterized by elevated levels of reactive oxygen species and a compromised response to oxidative stress in PPM1D -mutant cells. Altogether, our results demonstrate a role for SOD1 in the survival of PPM1D -mutant leukemia cells and highlight a new potential therapeutic strategy against PPM1D -mutant cancers.